A perspective on Trans-speciesism through Enoch, a Character in Flannery O’Connor’s Novel «Wise Blood» - Miró López, Susana (Pensamiento. Revista de Investigación e Información Filosófica, 2025)
This study analyses trans-speciesism. It has been defined, shown its origin and evolution, listed its main features and objectives. It is identified as a phenomenon in connection with transhumanism/post-humanism. After presenting the state of the question, a study of people who claim to be trans-species is proposed in the light of Enoch, a character in Flannery O’Connor’s Wise Blood. With this dialogue between trans-speciesism and the Anthropology that underlies the novel, a possible connection is made between Enoch’s quest and the longings that can motivate identity changes in trans-species people.